PEMANFAATAN LIMBAH TONGKOL JAGUNG DAN GETAH KARET SEBAGAI BAHAN BAKU DALAM PEMBUATAN BIOBRIKET - Astri Jayanti; Adelina Adriani; Meri Kristiani; Arie Hapsani Hasan Basri (Politeknik Pembangunan Pertanian Medan, 2020)
Biomass is a potential source of energy developed as an alternative source of substitute for fossil fuels and can be renewed. One of the fuels derived from biomass is corncob biobriquette waste. Thisstudy aims to determine the characteristics of physical properties (heat value and density) chemical properties (water content, ash content, levels of flying matter, and carbon content) and endurance (stability and strength). This research method was experimental, namely direct observation through the carbonization process and quantitative data measurement. The adhesive used is starch and aquadest with a ratio of 1: 4, to measure the heating value of briquettes using a bomb calorymeter. From the research results of briquettes A, B, and C, it can be seen that the physical properties, chemical properties and durability produced are apparently not much different compared to coal briquettes. The highest heating value produced by coal briquettes is around 6.058,62 cal/g while the heating value in composition A biobriquette is 5.956,21 cal/g, composition B is 5.241,78 cal/g and the lowest heating value is found in composition C biobriquette namely 4,935.91cal/g. The results showed that biobriquette from corn cobs and rubber latex with compositions A and B were still in accordance with SNI.